The Effectiveness of Mediation as a Dispute Resolution for e-book Copyright Infringement Cases in Indonesia: (Case Studies Occurring in the Jakarta and Riau Areas) - M. Sanusi Helmi; Muhammad Noor Ridani; Muhammd Haris; Sulistyoko, Arie (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT The effectiveness of Mediation as a dispute resolution of e-book copyright infringement cases in Indonesia related to case studies that occurred in Jakarta and Bandung is more precisely regulated in Law Number 28 of 2014 concerning Copyright. The problem of this research is how examples of e-book copyright infringement cases and how the effectiveness of Mediation in resolving disputes over e-book copyright infringement. The objectives of this study are, first, to determine the forms of copyright infringement relating to e-books. Second, to review and analyze the effectiveness of mediation as a settlement of copyright infringement disputes in the manufacture of e-books through cases that have occurred in the Republic of Indonesia. The research method used is the normative juridical method. This method specializes in legal principles, namely UUHC. The results showed that the forms of copyright infringement in the manufacture of e-books, namely, first, pirates make copies (unauthorized copies) of e-books illegally, hidden and unknown to others, let alone law enforcement and taxation. second, downloading e-books with the aim of distribution or for commercial purposes. third, printing e-books that have been purchased is included in the act of copying creation. fourth, changing the format of a book into an e-book and including the author's name without prior notice to the author of the book is included in the category of infringement. The effort found in both cases is mediation through the DJKI institution in accordance with the provisions of Article 95 paragraph (4) of the UUHC which expressis verbis regulates that criminal charges can only be filed if the parties to the dispute have taken mediation efforts, this regulation is the ultimum remedium. Keywords : E-Books, Mediation, Copyright Infringement. ABSTRAK Efektivitas Mediasi sebagai penyelesaian sengketa kasus pelanggaran hak cipta e-book di Indonesia terkait studi kasus yang terjadi di Jakarta dan Bandung lebih tepatnya diatur dalam Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. Permasalahan penelitian ini adalah bagaimanakah contoh kasus pelanggaran Hak Cipta e-book dan bagaimanakah efektivitas Mediasi dalam menyelesaikan sengketa terhadap pelanggaran Hak Cipta e-book. Tujuan dari penelitian ini adalah, pertama, untuk mengetahui bentuk-bentuk pelanggaran hak cipta yang berkaitan dengan e-book. Kedua, untuk mengkaji dan menganalisis efektivitas mediasi sebagai penyelesaian sengketa pelanggaran hak cipta dalam pembuatan e-book melalui kasus-kasus yang pernah terjadi di Negara Republik Indonesia. Metode penelitian yang digunakan adalah metode yuridis normatif. Metode ini mengkhususkan pada asas-asas hukum yaitu UUHC. Hasil penelitian menunjukkan bahwa bentuk-bentuk pelanggaran hak cipta dalam pembuatan e-book yaitu, pertama, pembajak membuat salinan (copy tanpa izin) e-book secara ilegal, tersembunyi dan tidak diketahui oleh orang lain, apalagi penegak hukum dan perpajakan. kedua, mengunduh e-book dengan tujuan untuk disebarkan atau untuk tujuan komersil. ketiga, mencetak e-book yang sudah dibeli termasuk dalam perbuatan menyalin ciptaan. keempat, merubah format sebuah buku menjadi e-book dan mencantumkan nama pengarangnya tanpa ada pemberitahuan terlebih dahulu kepada pengarang buku tersebut sudah termasuk dalam kategori pelanggaran. Upaya yang ditemukan pada kedua kasus tersebut adalah mediasi melalui lembaga DJKI sesuai dengan ketentuan Pasal 95 ayat (4) UUHC yang secara expressis verbis mengatur bahwa tuntutan pidana baru dapat diajukan apabila para pihak yang bersengketa telah menempuh upaya mediasi, peraturan ini bersifat ultimum remedium. Kata Kunci : E-Book, Mediasi, Pelanggaran Hak Cipta.